2019
DOI: 10.1177/0021998319850874
|View full text |Cite
|
Sign up to set email alerts
|

Finding the best sequence in flexible and stiff composite laminates interleaved by nanofibers

Abstract: The brittle nature of thermoset-based composite laminates restricts the application of these materials in various industries. One of the most effective methods for resolving this problem is interleaving the laminate by nanofibrous mats. Applying nanofibers between all layers is very costly and time-consuming. Therefore, the efficiency of using nanofibers in half of the layers for various interleaf sequences is investigated in this study. On the other hand, since the damage pattern is different in thick and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…18 Some studies have also focused on the suitability of interleaving techniques to improve LVI damage resistance and tolerance. [19][20][21][22][35][36][37][38][39] García-Rodríguez et al 19 interleaved two types of coPA veils, with identical areal weights and different melting temperatures, between each ply of a quasi-isotropic laminate. They observed that veils that have melted during the composites manufacturing process have reduced LVI damage and enhanced residual strength in CAI tests.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Some studies have also focused on the suitability of interleaving techniques to improve LVI damage resistance and tolerance. [19][20][21][22][35][36][37][38][39] García-Rodríguez et al 19 interleaved two types of coPA veils, with identical areal weights and different melting temperatures, between each ply of a quasi-isotropic laminate. They observed that veils that have melted during the composites manufacturing process have reduced LVI damage and enhanced residual strength in CAI tests.…”
Section: Introductionmentioning
confidence: 99%
“…A few works can be found in the literature aiming at a selective interleaving approach. 38,39,43 Yi and An 43 spread a toughening agent, amorphous polyether ketone with phenolphthalein group (PEK-C), into a quasiisotropic laminate using different interleaving sequences. They concluded that the interleaving arrangement influences the impact damage and residual strength after impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using thermoplastics as additives in thermoset-based CFRPs is an attractive method for enhancing their fracture toughness [11][12][13][14]. These additives can be in the form of particles [15][16][17][18], film [19,20], or fibers [21][22][23][24][25][26], and range in size from nano-to micrometers. These types of materials have long been used for toughening laminates, except for nanofibers which were introduced in the last few years [27] and have not attracted researchers' attention until recently [28].…”
Section: Introductionmentioning
confidence: 99%
“…Literature reviews on nanofibers reinforcing composites are wide, and many polymers, such as polyvinylidene fluoride (PVDF) [17][18][19][20], polyvinyl butyral (PVB) [21][22][23], polysulfone (PSF) [10,11,24], Nylon [25][26][27][28][29][30][31][32], phenoxy [33,34], and carbon [35][36][37] nanofibers, have been used to enhance composites' mechanical properties. Saghafi et al [20] Showed that PVDF nanofibers can increase Mode-I fracture toughness by about 43%, while another study [19] in this field had completely reverse outcomes.…”
Section: Introductionmentioning
confidence: 99%